The Relationship Between Maternal Knowledge and Attitude Towards Post-immunization Adverse Event Reaction in Infants 0-24 Months: A Cross-sectional Study - Putri Mayang Sari; Wiwiet Susan Amelia (School of Health Sciences Al-Ma'arif, 2025)
Adverse Events Following Immunization (AEFI) often occur after every type of vaccination, including the DPT vaccine. Many children experience fever after receiving the DPT vaccine, which is a normal reaction. However, many mothers feel tense, anxious, and worried. This study aims to determine the relationship between mothers’ knowledge and attitudes towards AEFI reactions in toddlers receiving the DPT vaccine at the UPTD Tanjung Agung Community Health Center in 2024. The sampling technique used accidental sampling with a total of 65 respondents. The research instrument was a questionnaire, and data analysis was conducted bivariately using the chi-square test.The results of this study indicate a significant relationship between mothers’ knowledge of AEFI reactions. Mothers’ attitudes towards AEFI reactions and DPT immunization were also analyzed. The Chi-square analysis results show a significant relationship between mothers’ knowledge of AEFI reactions (p-value = 0.000) and their attitudes toward AEFI reactions (p-value = 0.000). Knowledge and attitudes towards AEFI reactions have a significant relationship with DPT immunization. It is concluded that there is a relationship between knowledge and attitudes about AEFI and the administration of the DPT vaccine. Therefore, healthcare workers are expected to improve DPT immunization and AEFI education to minimize negative perceptions regarding DPT immunization and AEFI.